Identitas Sosial dan Hedonisme di Laman Pribadi Selebgram - Natasya Intan Permatasari; Mutia Rahmi Pratiwi; Nalal Muna (CHANNEL: Jurnal Komunikasi, 2020)
Social media users tend to be "the center of attention". One of the social media that is widely used in Indonesia is Instagram and people who are popular on Instagram are called celebrities. Karin, through her Instagram account @awkarin, is one of the celebrities who appeared in 2018 with a controversial and hedonistic lifestyle. This research is qualitative research using the virtual ethnography method. The research object analyzed was the upload on the @awkarin page during 2019 which contained elements of hedonism. The theory used is the theory of identity presented by Tajfel and the theory of hedonism. The results showed that Karin through the @awkarin Instagram account has formed a virtual social identity by displaying personal orientation, individual values, and self-expression. The form of hedonism that refers to Awkarin on Instagram includes three things, namely: Activities, Interests, and Opinions. Hedonistic activities are shown by hangout, owning luxury items, and going with friends or partners to a cafe or fancy place. Karin's interest is shown by the items used and gathered in a special place for the middle and upper social classes. Karin's opinion is shown with comments to netizens who are pro and contra.